Analysis of Student Misconseptions Using Evaluation Tools Based Three Tier Multiple Choice - Zawawi, Irwani; Suryanti, Sri (Postulat : Jurnal Inovasi Pendidikan Matematika, 2022)
The purpose of this study was to identify and analyze the types of students' misconceptions on the geometry material of the quadrilateral sub-material. This type of research is descriptive quantitative. The research subjects were students of class VII SMPN 5 Lamongan as many as 120 students. The research instrument used was a three-tier multiple choice diagnostic test sheet. The result of the research is that 56.2% of students have misconceptions about the quadrilateral material, including the category of moderate misconceptions. From these misconceptions, the types of misconceptions are grouped into classificational misconceptions by 15%, correlational misconceptions by 19.1%, and theoretical misconceptions by 22.1%.